“Industrialisasi Novel Populer Indonesia Periode 1980-1990” - Noor, Redyanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Industrialization of Indonesian popular novel 1980-1990 period marked by the increasing of writing productivity. That increased caused by the increasing number of readers. The increasing number of readers caused by the growing tradition of reading due to the publication of magazines and newspapers containing fictional stories (short stories, serialized stories, novella). To meet the needs of the novel in large numbers, the novel is produced in mass. The massalization of popular novel production involves four supporting elements, namely authors, publishers, distributors, and consumers. The involvement of the four supporting elements suggests that popular novel has become a useful commodity which make it to produce with industrial systems and strategies. The popular novel industry is a leisure-class product which has a very strong business spirit. Popular novels are at the center of sophisticated and modern communication solutions. Business communication is related to a variety of professions that work synergistically. Every popular novel published is the collective work of editors, illustrators, graphic design, lay-outer, offset-operation, marketing, sales-promotion, and so on. Thus, popular novels can no longer be referred as the work of individuals but it can be referred as collective work that build upon industrial law.